Siła celebrytów w kampanii wyborczej - Olczyk, Tomasz (Political Preferences, 2015)
The strength of celebrities in the election campaign The article presents analysis of perceptions of electoral chances of celebrity candidates, and opinions about influence of celebrity endorsements on voters decisions among voters in the 2014 European Parliament elections and local elections in the same year in Poland.From 30% up to 50% of electorates of all except one party agree with the preposition that celebrities have bigger chances to win elections than traditional politicians. The only exception are voters of New Right of Janusz Korwin-Mikke. Up to 57% of electorates tend to agree with claims that celebrity endorsement have significant influence on voters decision. In this case neither party identification nor declared ideology is significant differentiator. These findings interpreted in terms of the low information rationality theory suggest that utilisation of celebrity in electoral campaings my serve as an important cue for a low information voters. Key words: celebrity politician, celebritization, celebrities, election campaign